(untitled) (Kinesiology, 2022)
The use of cupping therapy prior to sports events has increased in popularity, with limited evidence to support its efficacy. The purpose of this study was to evaluate the efficacy of dry and wet cupping therapy on subsequent Wingate anaerobic test (WAnT) performance. Twelve trained men participated in this repeated measures randomized crossover study (age 24.9 ± 4.8 years; body mass index 27.6 ± 14.3 kg.m-2). Participants were familiarized with the ergometer and the Wingate anaerobic test on three separate occasions. They then randomly performed three experimental Wingate tests separated by 48-72 h after either dry cupping (DRY), wet cupping (WET), or no treatment (CON). Repeated measures ANOVA and Pearson’s correlation coefficient were used to analyze data and determine the relationships between WAnT and peak lactate and heart rate (HR). Peak power (PP), mean power (MP), and fatigue index (FI) were similar in all treatments (p=.47-.72). Heart rate (HR) and lactate increased similarly at all time points in all treatments (p<.001 for all comparisons). Post-WAnT peak HR was moderately negatively correlated with PP in all treatments and MP in CON only (p<.05 for all correlations). No other significant correlations were detected. The present findings demonstrate no beneficial effects of wet and dry cupping therapy, and hence do not support its use prior to high-intensity anaerobic sports events. Key words: Wingate test, anaerobic power, fatigue, sprint cycling, all-out exercise performance, bloodletting cupping